2012
DOI: 10.3109/00016357.2012.734411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of masticatory muscle training on maximum bite force and muscular endurance

Abstract: For both the continuous and intermittent training groups, 4 months of chewing exercises strengthened masticatory muscles, but such effects diminished gradually for both groups when the exercises stopped.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
0
14
0
4
Order By: Relevance
“…Several previous studies reported that changes in major masticatory muscle seemed to have a greater impact on masticatory efficiency . However, mastication is a dynamic and complex process caused by a combination of factors such as biting force, masticatory muscle activity, swallowing threshold, as well as intra‐oral status such as salivary secretion and occlusal position .…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies reported that changes in major masticatory muscle seemed to have a greater impact on masticatory efficiency . However, mastication is a dynamic and complex process caused by a combination of factors such as biting force, masticatory muscle activity, swallowing threshold, as well as intra‐oral status such as salivary secretion and occlusal position .…”
Section: Discussionmentioning
confidence: 99%
“…The influence of training is a fundamental issue that would be worth exploring further. Indeed, exercise can improve masticatory function (Bourke et al, 2008;He et al, 2013;Kiliaridis et al, 1995;Kim et al, 2018;Lindner et al, 1995;Shirai et al, 2018;Thompson et al, 2001) but few studies have investigated this in detail.…”
Section: Determinants Of Bite Forcementioning
confidence: 99%
“…In a study by Kim et al [47], the MAI was significantly increased after only 8 weeks of simple oral exercises; further, Morita et al [23] reported that masticatory performance is associated with the muscle power of the whole body. Therefore, strengthening the muscle function of the oral and maxillofacial region will improve not only masticatory performance [48] but also the overall physical performance of the elderly [2].…”
Section: Discussionmentioning
confidence: 99%